Influence of organic and inorganic plant nutrient sources on nutrient content and uptake in wheat (Triticum aestivum L.) - RAI, TRILOK NATH (Journal of Soil and Water Conservation, 2020)
An investigation was carried out to study the influence of organic and inorganic plant nutrient sources on nutrient content and uptake in wheat (Triticum aestivum L.) of variety HUW-533. The pot culture experiment was laid in Completely Randomized Block Design with twelve treatments replicated three times. N, P, K were applied through urea, single super phosphate and muriate of potash, respectively. While the total amount of organics were applied 7 days before sowing of the wheat. The results indicated that the application of N through 120 kg ha-1 by urea and 10 kg ha-1 through different organic sources increase the N, P and K contents significantly (except K in grain) in grain and straw. Poultry manure resulted in higher N content in grain and straw; however the uptake was maximum in grain as carpet waste and in the straw as poultry manure but total uptake of N were maximum and minimum recorded in the treatment of 100% NPK + 10 kg N ha-1 through C.W. and control, respectively. Total P and K content and their uptake were maximum in the treatment of in grain and straw. The results of N content in the treatments were at par; most of the similar trends were found in the case of P and K content.